Composition and petroleum potential of lake facies in the FA-MS-48-73 well, mae soon structure, Fang oilfield, Northern Thailand - A. Foopatthanakamol (2018)
The Fang Basin is one of a series of Cenozoic rift-related structures in northern Thailand. The Fang oilfield includes a number of structures including the Mae Soon anticline on which well FA-MS-48-73 was drilled, encountering oil-filled sandstone reservoirs at several levels. Cuttings samples were collected from the well between depths of 532 and 1146 m and were analysed for their content of total organic carbon (TOC, wt%), total carbon (TC, wt%) and total sulphur (TS, wt%); the petroleum generation potential was determined by Rock-Eval pyrolysis. Organic petrography was performed in order to determine qualitatively the organic composition of selected samples, and the thermal maturity of the rocks was established by vitrinite reflectance (VR) measurements in oil immersion. The TOC content ranges from 0.75 to 2.22 wt% with an average of 1.43 wt%. The TS content is variable with values ranging from 0.12 to 0.63 wt%. Rock-Eval derived S 1 and S2 yields range from 0.01-0.20 mg HC/g rock and 1.41-9.51 mg HC/g rock, respectively. The HI values range from 140 to 428 mg HC/g TOC, but the majority of the samples have HI values >200 mg HC/g TOC and about one-third of the samples have HI values above 300 mg HC/g TOC. The drilled section thus possesses a fair to good potential for mixed oil/gas and oil generation. On an HI/Tmax diagram, the organic matter is classified as Type II and III kerogen. The organic matter consists mainly of telalginite (Botryococcus-type), lamalginite, fluorescing amorphous organic matter (AOM) and liptodetrinite which combined with various TS-plots suggest deposition in a freshwater lacustrine environment with mild oxidising conditions. Tmax values range from 419 to 436°C, averaging 429°C, and VR values range from ∼0.38 to 0.66% R 0 , indicating that the drilled source rocks are thermally immature with respect to petroleum generation. The encountered oils were thus generated by more deeply buried source rocks. © 2008 Scientific Press Ltd.